Does Preoperative Waiting Time Affect the Short-Term Outcomes and Prognosis of Colorectal Cancer Patients? A Retrospective Study from the West of China - Xiao-Yu Liu; Zi-Wei Li; Bing Kang; Yu-Xi Cheng; Wei Tao; Bin Zhang; Hua Zhang; Zheng-Qiang Wei; Dong Peng (Canadian Journal of Gastroenterology and Hepatology)
Purpose. The purpose of this study is to analyze the effect of preoperative waiting time on the short-term outcomes and prognosis in colorectal cancer (CRC) patients. Methods. We retrospectively analyzed 3744 CRC patients who underwent primary CRC surgery at a single clinical medical center from Jan 2011 to Jan 2020. The baseline information, short-term outcomes, overall survival (OS), and disease-free survival (DFS) were compared among the short-waiting group, the intermediate-waiting group, and the long-waiting group. Results. A total of 3744 eligible CRC patients were enrolled for analysis. There were no significant differences in all of the baseline information and short-term outcomes among the three groups. In multivariate analysis, older age (OS: p=0.000, HR = 1.947, 95% CI = 1.631–2.324; DFS: p=0.000, HR = 1.693, 95% CI = 1.445–1.983), advanced clinical stage (OS: p=0.000, HR = 1.301, 95% CI = 1.161–1.457; DFS: p=0.000, HR = 1.262, 95% CI = 1.139–1.400), overall complications (OS: p=0.000, HR = 1.613, 95% CI = 1.303–1.895; DFS: p=0.000, HR = 1.560, 95% CI = 1.312–1.855), and major complications (OS: p=0.001, HR = 1.812, 95% CI = 1.338–2.945; DFS: p=0.006, HR = 1.647, 95% CI = 1.153–2.352) were independent factors of OS and DFS. In addition, no significant difference was found in all stages (OS, p=0.203; DFS, p=0.108), stage I (OS, p=0.419; DFS, p=0.579), stage II (OS, p=0.465; DFS, p=0.385), or stage III (OS, p=0.539; DFS, p=0.259) in terms of OS and DFS among the three groups. Conclusion. Preoperative waiting time did not affect the short-term outcomes or prognosis in CRC patients.